Implementasi Program PPL Terbimbing dan Mandiri untuk Mengoptimalkan Kompetensi Mengajar Calon Guru di SMPN 13 Lhokseumawe - Muhami, Hasina; Tahara, Dinda; Rahmatun, Ulfa; Dayusman, Edo Alvizar (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to evaluate the implementation of the Guided and Independent Field Experience Program (PPL) at State Junior High School 13 Lhokseumawe, conducted in 2024. The research method employed is qualitative, using an action research approach to evaluate and enhance the teaching competencies of prospective teachers during the PPL. Data collection techniques include observation, interviews, and documentation to gather information about students' experiences across the four stages of PPL: planning, implementation, observation, and reflection. The results show that each stage of PPL provides valuable experience for student teachers, with a focus on developing classroom management skills, teaching techniques, and integration of character education values in learning. The main challenges faced by students are effective classroom management, declining student interest in learning in the digital era, and changing attitudes towards educators. The implications of this study indicate the need for the development of more creative classroom management skills, the use of technology in learning, and strengthening professional reflection in developing prospective teachers' competencies.